THE IMPORTANCE AND NEW OPPORTUNITIES OF INVESTING IN HUMAN CAPITAL IN THE TOURISM SECTOR UNDER THE DEVELOPMENT OF THE DIGITAL ECONOMY - Abdurakhimova , Adiba Gayratovna (THE INNOVATION ECONOMY, 2026)
This article analyzes the significance and new opportunities of investing in human capital in the tourism sector in the context of digital economy development. The digital transformation of tourism plays a key role in improving service quality, implementing innovative technologies, and enhancing international competitiveness. The study highlights the preparation of qualified personnel, the development of their digital skills, and the economic efficiency of investments in human capital. The results indicate that investing in human capital is essential for ensuring the sustainable development of the tourism industry.